A safe and simple technique for exchanging central venous catheters. Issue 808 (February 1993) - Shimada, M.; Matsumata, T.; Wakiyama, S.; Maeda, T.; Kanematsu, T.; Sugimachi, K.
Abstract : A safe and simple technique for exchanging central venous catheters is herein described. Our technique is based on a modification of Seldinger's method, in which a new outer sheath is introduced over the previous catheter as a guidewire in order to simplify the exchange of central venous catheters. This technique can be successfully performed by new residents and can be applied to the exchange of clotted catheters.